Reinventing the Kebun Raya in the New Republic: Scientific Research at the Bogor Botanical Gardens in the Age of Decolonization - Goss, Andrew (Studium, 2019)
This essay discusses the efforts of Dutch, Japanese, and Indonesian scientists and officials to decolonize the scientific institutions in Indonesia, through the reinvention of scientific research and education at the Botanical Gardens in Buitenzorg (now the Kebun Raya Bogor). The essay describes successive efforts to rethink the science in Bogor between 1931 and 1955, first during the global economic depression, then during the Japanese occupation and the Revolution, and finally during the beginning of the Indonesian Republic. I examine this process by analyzing debates about the centralization of scientific authority, the internationalization of scientific collaboration, and the place of education within scientific institutes. I argue that political changes created new opportunities for the reinvention of science at the Botanical Gardens, with a focus on international collaboration such as the Flora Malesiana project, and by the mid-1950s, an educational mission to train the first generation of Indonesian researchers.